PlonArq: gerenciamento eletrônico de documentos arquivísticos baseado em software livre - Lucca, Giana (2007)
Document management is a key issue to any modern organization. In order to efficiently cope with managing large document sets, many organizations employ Electronic Document Management (EDM) systems. Although many EDM software solutions currently exist, there are few alternatives based on Free Software, i.e., computer programs which can be freely used, shared, studied, modified and redistributed by their users. Moreover, most EDM systems do not take into account some rules and recommendations issued from archivistics, that is a science which concerns itself with managing the document life cycle inside any organization. In such context, this work aims to associate archival principles for document management with the advantages of Free Software, as an approach to develop an original and flexible EDM software, which can be easily adapted to what an organization needs. To achieve this goal, we performed a requirements analysis for archival document management systems and designed a software system named PlonArq, which provides users with fundamental instruments for document management. We implemented this software as an extension of Plone, a largely usedWeb content management system. In order to validate PlonArq functionalities, we conducted a software evaluation from a final user point of view. As a result of this work, we obtained an EDM software which can be enhanced and distributed as a Free Software product. Another result is a data model which complies to several archival rules and recommendations and could be a starting point for developing new EDM systems.